The Bus Ride - Miller, William (New York Lee & Low Books Inc., 1998)
A black child protests an unjust law in this story loosely based on Rosa Parks' historic decision not to give up her seat to a white passenger on a bus in Montgomery, Alabamaz, in 1955.
Keywords: Afro-Americans - Fiction; Race relations - Fiction